Pharmaceutical properties of 'sucupira' (Pterodon spp.) - Daiane Hansen; Mitsue Haraguchi; Antonio Alonso (Universidade de São Paulo, 2010)
The plant of the genus Pterodon (Fabaceae, Leguminosae), commonly known as 'sucupira' or 'faveira', are disseminated throughout the central region of Brazil and has frequently been used in popular medicine for its anti-rheumatic, analgesic, and anti-inflammatory properties. In recent years, interest in these plants has increased considerably. The biological effects of different phytoextracts and pure metabolites have been investigated in several experimental models in vivo and in vitro. The literature describes flavonoids, triterpene and steroids, while one paper presented studies with proteins isolated from the genus. This review provides an overview of phytochemical and pharmacological research in Pterodon, showing the main chemical compounds studied to date, and focusing on the relationship between these molecules and their biological activity. Furthermore, this study paves the way for more in-depth investigation, isolation and characterization of the molecules of this plant genus. As plantas do gênero Pterodon (Fabaceae/Leguminosae), conhecidas popularmente como "sucupira branca" ou "faveira", encontram-se distribuídas pela região central do Brasil e são frequentemente utilizadas na medicina popular por suas propriedades antirreumáticas, analgésicas e antiinflamatórias. Nos últimos anos, o interesse por estas plantas tem aumentado consideravelmente. Os efeitos biológicos dos diferentes fitoextratos e metabólitos puros têm sido investigados em vários modelos experimentais in vivo e in vitro. A literatura descreve flavonóides, triterpenos, esteróides e apenas um trabalho mostra estudos com proteínas isoladas do gênero. Esta revisão apresenta de maneira geral as investigações farmacológicas e fitoquímicas de Pterodon, mostrando os principais compostos já estudados, sua composição química, focando na relação entre estas moléculas e sua atividade biológica. Mais ainda, nós abrimos as portas para maior investigação, isolamento e caracterização de moléculas deste gênero de plantas.